Oportunidades e desafios para a implantação de mini refinarias de petróleo como alternativa de suprimento da demanda futura de combustíveis no Brasil - Silvério, Carlos Augusto Noronha. (2018)
Along with the perspective of recovery of Brazilian economy, projections for petroleum-derived fuels demand move towards a strong growth and increase of internal supply deficits in long term. Distribution logistics structure and Brazilian refining capacity meets most of current demand. However, petroleum prices shrinkage and new Petrobras politics on product prices following international market trends granted favorable conditions to fuel importations through new players. Attempt for increasing internal supply by means of refining megaprojects does not succeed, following worldwide statistics related to this issue. Therefore, the current dissertation proposes the implementation of mini refineries as option to increase internal demand of fuels, appraising two possible configurations according to economic feasibility, competitiveness and exposure to technical, market and project management related risks through its life cycle. Results indicate a faster implementation and minor risk exposure mostly during execution phase. In the other hand, mini refineries are more sensible to variations on market conditions and scale diseconomy related issues as petroleum processing capacity is reduced.